Effect of Obesity and Socioeconomic Status on Adolescents’ High School Students’ Intelligence Quotient in Baghdad City - Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2017)
Objective(s): To determine the effect of obesity and socioeconomic status upon adolescents’ high school students’ intelligence quotient in Baghdad City. Methodology: A descriptive design is carried throughout the study to determine the effect of obesity and socioeconomic status on adolescents’ high schools students’ intelligence quotient in Baghdad City for the period of January 7th 2017 to May 29th 2017. A non-probability, purposive sample, of (120) high school students, is selected. The sample is comprised of (12) students from 7th grade, (26) students from 8 th grade, (14) students from 9th grade, (35) students from 10th grade, (13) students from 11th grade, and (20) students from 12th grade. It is consisted of (47) males and (73) females; and age of (11-19) years old. A questionnaire has been constructed throughout the following procedures in order to achieve the aims of the study through review of relevant literatures and consultation from a panel of experts. The questionnaire is comprised of (50) item that measure the high school students’ intelligence quotient. The intelligence quotient is measured as poor (50-116.6), fair (116.7- 183.3), and good (183.4-250). A socioeconomic status scale is developed to measure the students’ socioeconomic status as high (26-29), moderate (16- 25), and low (5-10). A body max index (BMI) is measured to determine the students’ obesity as grade I, grade II and grade III. Content validity of the questionnaire is determined through panel of experts and the internal consistency reliability is determined for the study questionnaire with a split-half technique Cronbach alpha correlation coefficient is computed for such reliability. Findings indicate that the correlation coefficient is (r=0.87) which is considered adequate for the reliability of the questionnaire as measure for the phenomenon underlying the study. Data are collected through the use of the study instrument and the interview technique as means for data collection for the period of February 21st 2017 to March 20th 2017. Data are analyzed through the application of the descriptive data analysis approach which includes frequency, percent and total score. Results: Middle age and Female students experience low level of intelligence quotient more than others. Results of the study reveal that students’ obesity and socioeconomic status affect their scores of intelligence quotient. The study reveals that obesity can dramatically influence students’ intelligence quotient. Students with low and moderate socioeconomic status have experienced low scores of intelligence quotient. Recommendations: The study recommends that education program can be designed and implemented to parents of obese students in order to increase their awareness about the effect of obesity on students’ intelligence quotient. Special courses can be presented to obese students and those at the risk of obesity by which weight gain is avoided and/or treated. Further research can be conducted on large sample size with different characteristics.